Green Open Space Form/Morphology Characteristics Which Function Ecologically as Rain Water Absorber in Kalirungkut Subdistrict - Tisa Angelia; Haryo Sulistyarso; Eko Budi Santoso (Institut Teknologi Sepuluh Nopember, 2018)
Growth of development in Kalirungkut Subdistrict with the functioning of MERR IIC road since 2010 is rapidly happening. The rapid development took place in the areas of trade and services, settlements, and industry as well as education. The growth development that caused the land use change is not balanced with the availability of Green Open Space (GOS) which is adequate as ecological function of rainwater absorber, thus becoming one of the causes of flood/puddle in Kalirungkut Subdistrict. Green open space to absorb rain water is part of a green infrastructure that integrates with city drainage in the form of storage and water absorption. The purpose of this research is to identify the characteristic of green open space form / morphology as an ecological function of rainwater absorber in Kalirungkut Subdistrict, by looking at the existing research benchmarks, drawing the conclusions of the analysis and making it a guideline in the development of green open space of further absorbent rainwater. This study uses a comparative descriptive analysis method. The selection of descriptive-comparative analysis is conducted to describe the comparison of existing green open space with standardization and supporting theories in the provision and development of green open space as an ecological function of rainwater absorber based on the aspects of existing research. The result of this research is the characteristic of the form/morphology of Green Open Space as ecological function of rainwater absorber in Kalirungkut Subdistrict which consists of Green Open Space form which functioned as water body in the form of water retention, the availability of garden & sports field, various types of vegetation and supporting material, Appropriate Green Open Space, and Absorption Ability of this type of land cover